Konstruksi Sosial Praktek Kesetaraan Gender di Wahidiyah - Sardjuningsih, (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
The practice of gender equality in religious settings is often the subject of controversy and debate. This article examines the social construction of gender equality practices implemented in Wahidiyah, an Islamic religious institution that includes Shalawat Wahidiyyah, Islamic Boarding Schools, and Islamic Education Institutions, from kindergarten to university level. This study uses a sociological approach and Social Construction theory analysis to understand how the practice of gender equality in Wahidiyah is realized and understood by its congregation. Through qualitative data collection involving interviews, observations, and analysis of relevant documents, this study analyzed various aspects of social construction involved in the practice of gender equality in Wahidiyah. The results show that the practice of gender equality in Wahidiyah is a social reality that is deliberately built to dynamise the organization. The selection of leadership figures in institutions under Wahidiyah is based on individual qualifications and competencies regardless of gender. This social construction is seen by the congregation as a vehicle for healthy competition, where every congregation who has the qualifications and competencies in accordance with the needs of the organization has the opportunity to become part of the leadership. However, it is important to note that this pattern was not based on open elections. Instead, these individuals are appointed by the Muallif, taking into account loyalty, ability, and relevant educational qualifications. The practice of gender equality in Wahidiyah, in this way, reflects the existence of social constructs that lead to the building of a dynamic and inclusive organization. This article contributes to broadening our understanding of the practice of gender equality among Muslims, particularly in the Pesantren context. By focusing on aspects of social construction, this article presents a more comprehensive perspective on how the practice of gender equality in Wahidiyah is implemented and interpreted through its congregation.